If it's not what You are looking for type in the equation solver your own equation and let us solve it.
11-5x=10-x
We move all terms to the left:
11-5x-(10-x)=0
We add all the numbers together, and all the variables
-5x-(-1x+10)+11=0
We get rid of parentheses
-5x+1x-10+11=0
We add all the numbers together, and all the variables
-4x+1=0
We move all terms containing x to the left, all other terms to the right
-4x=-1
x=-1/-4
x=1/4
| x+3(6)=12 | | 60-b=31 | | 25+4f=81 | | 42/s=6 | | -11-8x=−-3x+19 | | 2(15-5x)=-3(21-2x) | | 123-3h=45 | | j/7-10=14 | | 3x+x-2=-78 | | S^2+s^2=169 | | 9-t=2 | | 335=-42+13v | | 2w+-2=-14 | | 35+15+0.25x=40+0.25x | | -13v=1195 | | 3x+30=12x+12 | | 4(35-2x)=2x+14 | | 6=1/3(x) | | -0.5=p/3-1.9 | | 3t+-1=-4 | | -2k+5=3 | | 16x–16=4 | | 0.59x+36=1.19x | | 2+-2s=10 | | 5x-28=-3(x-12) | | y=1/3(-18) | | x+16+x-2=28 | | -12x^2+20x-3=0 | | 0.59x+36=1.19 | | 2-(-s)=-0.3 | | -4j+-4=-20 | | 0.59x+36=1.19= |